WRITE NOISE IN MAGNETIC RECORDING - Hedeman, Walter R., Jr. (International Foundation for Telemetering, 1985)
International Telemetering Conference Proceedings / October 28-31, 1985 / Riviera Hotel, Las Vegas, Nevada === A novel source of noise is identified and described in this study. If a continuous recording medium is less than perfectly uniform, a given quantity may be recorded differently at different locations in the medium. Inadvertent “encoding” occurs, embedding noise in the signal. Symmetrical sideband noise power results from amplitude and phase modulation of the signal stream by the nonuniform recording medium. “Write noise”, so-called because writing is required, is correlated in amplitude with signal amplitude, and its mean frequency is the signal frequency. It is the dominant noise source for the current generation of recorders and tapes; its power spectrum is almost the same as the power spectrum of the signal. The ratio of standard deviation to mean value of the signal envelope when recording cw signals is an absolute measure of tape quality independent of record level, tape speed, and track width, and establishes an available signal-to-noise ratio which cannot be exceeded. It is assumed that the recorder output has a normal amplitude distribution about its mean value. Theory is confirmed by experiment, within experimental error, for cw and digital recording.